“Auditoria de Control Interno al Área de Crédito a la Cooperativa de Ahorro y Crédito Innovación Andina, Agencia Matriz, provincia de Cotopaxi, Año 2022” - Gallardo Salazar, David Alejandro (2024)
The current integrative project focused on the internal control assessment and improvement in the credit area from Andina Innovation Savings and Credit Cooperative. The study arises in response to the internal control growing importance in financial institutions for preventing fraud, errors and operational risks. For achieving this aim, it was designed a methodological framework, what includes a non-experimental approach, along with descriptive and field research. It was used two main instruments: interviews directed at the manager and the entity's staff, which allowed to collect information about the staff processes, controls and perceptions, regarding the internal control system, and a questionnaire based on the COSO III comprehensive framework that allowed to evaluate and strengthen the institution internal control, which is composed 47 questions distributed into five components. In relation to control activities, it was found what there are established procedures for granting and monitoring credits, although, these must be more rigorous, in information verification terms provided by applicants and the payment capacity assessment. The main results show, which the entity's credit area has a 67.29% high confidence level and a 32.91% low risk level. However, it was observed, what the component related to risk assessment has a 69% moderate confidence level and a 31% risk level. Further, it was elaborated the audit report by detailing the found findings, based on which, they can be taken the necessary corrective measures.